Ultrastructural features of the glandular region of the stomach of Piaractus mesopotamicus (Holmberg, 1887) with emphasis on the oxyntopeptic cell - Aires, E. D.; Dias, E.; Orsi, A. M. (Editrice Compositori Bologna, 1999)
The characteristics of the lining and glandular epithelial types of the wall of the stomach of pacu (Piaractus mesopotamicus Holmberg, 1887) were studied by transmission electron microscopy. Columnar mucous cells were observed in the lining epithelial surface and the glandular epithelium that invaginated in the lamina propria showed secretory cells or oxyntopeptic cells as called by some authors in the literature. The columnar epithelial cells are narrow and show a basal nucleus. They are rich in organelles and contain secretory granules of round or rectangular shape heterogeneously electron dense in the apical portion. In the basal region of the glands there are secretory cells. The luminal half of these cells has abundant tubules (tubulo-vesicular system) that communicate with the external medium. Deeper basally in the cytoplasm there are the nucleus, mitochondria of various shapes and other scattered organelles.
Keywords: stomach; ultrastructure; Piaractus mesopotamicus